LID and LETID evolution of PV modules during outdoor operation and indoor tests - Fokuhl Esther (EDP Sciences, 2021)
Light Induced Degradation (LID) and Light and Elevated Temperature Induced Degradation (LETID) manifest with carrier injection due to light or forward bias and can lead to performance losses during the first months or years of operation in the field. We are investigating the effects of common LETID indoor test conditions and the module temperature under outdoor exposure on the evolution of BO LID and LETID over time. The investigations are based on experimental data from twelve structurally identical mono-crystalline and two multi-crystalline PERC PV modules, which underwent a detailed experiment including five different indoor test sequences and an outdoor test. Changes in the module performance are discussed based on the current knowledge on state transitions of the BO defect and LETID. Temporary recovery of the LETID defect was used to distinguish LETID from other degradation mechanisms. Our results confirm the importance of BO stabilization prior to LETID tests as it is included in the current IEC TS draft for LETID detection. We also show that too strong acceleration of the processes can lead to misinterpretation of LETID test results. Under dark storage conditions, destabilization of BO defects was found to already evolve at temperatures as low as 75 °C and a likely alteration of subsequent LETID was observed. The performance changes under outdoor exposure can be explained with the same mechanisms as investigated under indoor experiments and reveal reversible seasonal recovery effects. Furthermore, the influence of different module operating temperatures on the evolution of both, BO LID and LETID is presented and evaluated.